Vulnerable asset management? The case of mutual funds - Christoph Fricke; Daniel Fricke (Deutsche Bundesbank, 2017)
Is the asset management sector a source of financial instability? This paper contributes to the debate by performing a macroprudential stress test in order to quantify systemic risks in the mutual fund sector. For this purpose we include the welldocumented flow-performance relationship as an additional funding shock in the model of Greenwood et al. (2015), where systemic risks arise due to funds' fire sales of commonly held assets. Using data on U.S. equity mutual funds for the period 2003-14, we quantify both fund-specific and aggregate vulnerabilities to fire-sales over time. Our main finding is that the funds' aggregate vulnerability according to this propagation mechanism is generally small. We explore the determinants of individual funds' vulnerability to systemic asset liquidations, highlighting the importance of funds' liquidity transformation. Therefore, regulators should monitor structural vulnerabilities in the fund sector arising through liquidity transformation.
Keywords: G10; G11; G23; 330; asset management; mutual funds; systemic risk; fire sales; liquidity